Catchment precipitation processes in the San Francisco valley in southern Ecuador: combined approach using high-resolution radar images and in situ observations - Oñate Valdivieso, F. (2017)
The precise estimation of precipitation quantities in tropical mountain regions is in great demand by ecological and hydrological studies, due to the heterogeneity of the rainfall distribution and the lack of meteorological station data. This study uses radar images and ground station data to provide the required high-resolution precipitation maps. Also wind data are taken into account, due to its influence on the precipitation formation and to demonstrate the relation between synoptic wind, topography and the precipitation distribution inside small mountain valleys. The study analyses the rainfall distribution and amounts of 4 days inside the San Francisco Valley, a small catchment in the tropical Andes of southern Ecuador, representing different seasons and the typical atmospheric flows, which are correlated to the annual precipitation map. The results show that the rainfall distribution and amounts are generally defined by the wind direction and velocity, besides the topographic location in relation to the main barriers and pathways. The dominant wind direction causes a division of the catchment in a wetter eastern and a dryer western part. Moreover, the annual seasons are reversed; the main rainy season for the eastern part occurs between June and August, while the western part reaches the precipitation maximum between January and March. This may have influence on the species composition at the different slopes and the annual hydrological cycle inside the catchment.